ShRNA‐mediated PPARα knockdown in human glioma stem cells reduces in vitro proliferation and inhibits orthotopic xenograft tumour growth. Issue 4 (27th December 2018) - Haynes, Harry R; Scott, Helen L; Killick‐Cole, Clare L; Shaw, Gary; Brend, Tim; Hares, Kelly M; Redondo, Juliana; Kemp, Kevin C; Ballesteros, Lorena S; Herman, Andrew; Cordero‐Llana, Oscar; Singleton, William G; et al.
Abstract: The overall survival for patients with primary glioblastoma is very poor. Glioblastoma contains a subpopulation of glioma stem cells (GSC) that are responsible for tumour initiation, treatment resistance and recurrence. PPARα is a transcription factor involved in the control of lipid, carbohydrate and amino acid metabolism. We have recently shown that PPARα gene and protein expression is increased in glioblastoma and has independent clinical prognostic significance in multivariate analyses. In this work, we report that PPARα is overexpressed in GSC compared to foetal neural stem cells. To investigate the role of PPARα in GSC, we knocked down its expression using lentiviral transduction with short hairpin RNA (shRNA). Transduced GSC were tagged with luciferase and stereotactically xenografted into the striatum of NOD‐SCID mice. Bioluminescent and magnetic resonance imaging showed that knockdown (KD) of PPARα reduced the tumourigenicity of GSC in vivo . PPARα‐expressing control GSC xenografts formed invasive histological phenocopies of human glioblastoma, whereas PPARα KD GSC xenografts failed to establish viable intracranial tumours. PPARα KD GSC showed significantly reduced proliferative capacity and clonogenic potential in vitro with an increase in cellular senescence. In addition, PPARα KD resulted in significant downregulation of the stem cell factors c‐Myc, nestin and SOX2. This was accompanied by downregulation of the PPARα‐target genes and key regulators of fatty acid oxygenation ACOX1 and CPT1A, with no compensatory increase in glycolytic flux. These data establish the aberrant overexpression of PPARα in GSC and demonstrate that this expression functions as an important regulator of tumourigenesis, linking self‐renewal and the malignant phenotype in this aggressive cancer stem cell subpopulation. We conclude that targeting GSC PPARα expression may be a therapeutically beneficial strategy with translational potential as an adjuvant treatment. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.